INCREASING COMMUNITY PARTICIPATION IN MAINTAINING CLEANLINESS AND HEALTH TO REALIZE COMFORTABLE TOURISM VILLAGE IN THE VILLAGE OF RINDU HATI - Rina Delfina; Sardaniah Sardaniah (Caring : Jurnal Pengabdian Masyarakat, 2021)
A clean and healthy tourist village is the main attraction for visitors because the beautiful and clean environment makes visitors feel comfortable. Based on the results of the FGD conducted by the University of Bengkulu's LPPM in the village of Rindu Hati, several problems were found, such as the cleanliness of the village, the absence of a garbage disposal site. This of course can cause various problems for visitors and the community, one of which can affect public health and the environment. Efforts that can be made are the Guidance of Clean and Healthy Living Behaviors (PHBS) to create and preserve hygiene and health-oriented lifestyles in the community, so that people can be independent in preventing and overcoming the health problems they face. The purpose of this community service activity is to provide education to the Rindu Hati village community so that they can maintain environmental cleanliness and health through the proper and correct application of PHBS, improve community knowledge and skills in managing household waste and environmental waste, and improve community skills in disease management. environmental impacts and independently in preventing and overcoming the health problems it faces. The methods used are: health education, training and demonstration. The results of this community service activity show an increase in community participation in maintaining environmental cleanliness and health, this can be seen from the community's ability to implement PHBS and utilize waste that has economic value.